Comparatives Studies of Profitability Indicators for Corporate Sustainability - Rekoria, Manantsampa Mitondrarivo (Archives of Business Research, 2025)
This research examines the comparative profitability indicators in the context of corporate sustainability, aiming to provide robust insights that balance financial performance with environmental and social responsibility. The study seeks to establish a framework for evaluating profitability metrics that align with sustainable practices, addressing the growing demand for businesses to integrate sustainability into their core strategies. To achieve these objectives, the research employs a mixed-methods approach, blending quantitative financial analysis with qualitative case studies of corporations that have successfully embedded sustainability into their operations. Data collection involved reviewing corporate reports, sustainability assessments, and financial statements, supplemented by interviews with industry experts to enrich the analysis with practical insights. Key findings reveal that profitability indicators such as Return on Investment (ROI) and Earnings Before Interest and Taxes (EBIT) can be adjusted to account for investments in sustainable practices. Companies prioritizing sustainability tend to exhibit long-term financial resilience, with notable improvements in stakeholder trust and brand equity. Furthermore, the research highlights the importance of transparent reporting and innovative business models in achieving sustainable profitability. These findings underscore the significance of aligning corporate financial metrics with sustainability goals, paving the way for future research into sector-specific adaptations and broader implementation strategies.